“MANGGARAI TRANSIT HUB” TERINTEGRASI DENGAN HUNIAN VERTIKAL - Lucky Brian Hartono; Suwandi Supatra (Jurusan Arsitektur dan Perencanaan, 2022)
The city of Jakarta is now a center for mobility activities with various fields carried out by the community every day. However, the vastness of the city of Jakarta causes a lack of effective control and planning of space and functions in each area. Because of this, there is regional degradation and negative spaces such as slums and illegal settlements and abandoned buildings arise. In addition, less affordable modes of transportation between important places are present around the area. Therefore, it is necessary to have a building with the function of a housing program and public transportation transit space that is affordable by urban communities. The Manggarai area is a major transit center point that has existed since the Dutch colonial period and has a function as a large center for public transportation such as trains and city buses. However, it can be seen from the existing area, that there is no increase in regional development and the emergence of many negative and inefficient spaces in the use of space in the Manggarai area. One of issues is the slum settlement that have been built on the riverbanks and side of railway line, causing insufficient indoor and outdoor space in the Manggarai area. The design method is